Territorial Analysis of the European Rural Development Funds (ERDF) as a Driving Factor of Ecological Agricultural Production - Marcos Ferasso; Miguel Blanco; Lydia Bares (Agriculture, 2021)
The Europe 2030 project identified the need to create a growth model that is based on a dynamic balance between economic, social, and environmental dimensions. This involves, among other objectives, redirecting the resources that are allocated to the Common Agricultural Plan (CAP) toward more ecological agriculture and livestock. In recent decades, two packages of the European Agricultural Fund for Rural Development (EAFRD) approved funds for projects related to agriculture. This study carried out a regional evaluation of the effects on production and employment that were generated in the Spanish organic farming sector. For this, a methodology that is frequently used by researchers to analyze territorial differences was used, namely, the shift-share analysis. The main results showed important differences at the regional level in the production of crops. Likewise, constant shift and constant share analyses were used to forecast the evolution of the sector from the recent data. Pending the approval of the new EAFRD 2021–2030, the results obtained in this research allowed for the identification of the regions that showed a favorable evolution to change the agricultural model and to identify the projects that generated employment and ecological production in the sector.